Presença judaica: o passado colonial nas figurações familiares do sertão cearense - Lopes, Maria Ednanda Rodrigues (2022)
The proposal of sociological analysis discussed in this dissertation work seeks, in the underground of the historical past, to recall the trajectory of New Christians who came to Brazil, at the beginning of Colonization, in the face of the institutionalization of the faith machine. This institutionalization was characterized by the stigma and persecution against Jewish blood, being especially strengthened from a complex arrangement sewn between the Portuguese Monarchy and the Iberian Holy Office. In this perspective, the concepts of social processes and family figurations, by the German sociologist Norbert Elias, as well as collective and individual memory and the category of identity analysis are seen as central to understanding the relationships and reactions presented in the reality of Jewish descendants. Sephardic, in the current context of the metropolitan region of Sobral, State of Ceará. I will analyze the motivations of the candidates included in the Decree-Law, number: 30-A/2015, pages: 1246-(92) to 1246-(93), approved on February 27, 2015, by the Parliament of Portugal, which grants the right to Portuguese citizenship, by naturalization, to foreign citizens who prove through the required documentation, descent from Jews who were, in the mid-15th and early 16th centuries, forced to leave Portugal by virtue of the Inquisition. The subjects described in the present research were also confirmed in consultations in primary documentation, baptismal records, marriage records, obituaries, documental archives of notaries, museums, diocesan curia, among others.